Development of Management Information System and PBSI Athlete Database for Kendal Regency - Dyta Mukti Hertikasari; Sugiharto Sugiharto; Donny Wira Yudha Kusuma (STKIP Muhammadiyah Kuningan, 2022)
The purpose of this study was to produce a management information system product and the Kendal Regency PBSI athlete database, test the effectiveness and analyze the acceptance of the Kendal Regency PBSI athlete management information system and database product so that the system product can play a role in the data input process and make it easier for users to find information. The research method used is development research. The development procedure used includes several stages, namely; 1) research and data collection; 2) product planning, and 3) product development. The instruments used in this development research are questionnaires, observations and interviews. The subjects and places of research are PBSI administrators, club administrators, coaches and athletes under the auspices of PBSI Kendal Regency. This research aims to produce a website-based product management information system and database of PBSI athletes in the Kendal Regency that can be accessed via computers and smartphones so that it can be accessed anytime and anywhere. Test the product's effectiveness on a small group scale with an overall score of